Professional Development Strategies and Challenges Among Indonesian English Teachers - Muna Nurhayati Fadhillah; Enita Daulay; Farida Repelitawati Kembaren (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates the challenges faced by Indonesian English teachers in engaging with Continuing Professional Development (CPD), the strategies they employ to sustain professional growth, and the reasons underlying their preferences. Addressing three research questions—teachers’ CPD strategies, the rationale behind their choices, and the obstacles encountered—the study adopts a qualitative design using semi-structured interviews with five English teachers at different career stages. Data were analyzed thematically to identify recurring patterns related to strategies, motivations, and structural constraints. The findings reveal that teachers combine formal workshops, collaborative forums such as Musyawarah Guru Mata Pelajaran (MGMP), and self-directed online learning to enhance their professional competence. Strategy preference is strongly influenced by practicality, flexibility, classroom relevance, and immediate instructional impact. However, teachers face persistent barriers, including limited access to quality training, financial constraints, heavy administrative workload, and mismatches between CPD content and classroom realities. Differences across career stages also shape motivation and engagement, with novice teachers prioritizing confidence-building, mid-career teachers balancing administrative and instructional demands, and senior teachers emphasizing sustainability and reflective practice. Overall, CPD emerges as a negotiated process shaped by both structural conditions and teacher agency. The study underscores the importance of context-sensitive, accessible, and practice-oriented CPD supported by institutional alignment and equitable distribution of opportunities.